Cervical trauma : surgical management - Heary, Robert F. (Thieme, 2019)
The definitive textbook on the management of cervical spine trauma from master spine surgeons! Understanding the clinical implications of cervical trauma requires thorough knowledge of the anatomy and physiology of the cervical spine. Cervical Trauma: Surgical Management by renowned spine surgeon Robert Heary and a cadre of prominent neurosurgical and orthopaedic spine experts is the most comprehensive, state-of-the-art resource available to date on this topic. The text begins with discussion of cervical anatomy and the pathophysiology of spinal cord injury (SCI), SCI classification systems,